Analisa Sistem Pakar Diagnosa Penyakit Lambung Menggunakan Metode Forward Chaining - Ananda Safitri; Elang Pramana Putra; Muhammad Agung Prasetio; Widya Puspita Cahyani; Perani Rosyani (Shofanah Media Berkah, 2023)
Diagnosing gastric disease is a challenge in the medical field because of its often similar symptoms and the complexity associated with other factors that can affect a patient's condition. The expert system has become an interesting approach in diagnosing gastric diseases because of its ability to mimic the intelligence and knowledge of a medical expert. In this study, we conducted an analysis of the Gastric Disease Diagnosis Expert System using the Forward Chaining method with a Systematic Literature Review (SLR) approach. The Forward Chaining method is used for inference based on the rules and facts of the symptoms collected, while the Systematic Literature Review (SLR) is used to analyze the relevant literature to gain a comprehensive understanding of the use of the Forward Chaining method in the diagnosis of gastric diseases. The results of our analysis provide important insights into the implementation, advantages, solution and platfrom of using the Forward Chaining method in an expert system for diagnosing gastric diseases.